Rationalizing Choice Functions By Multiple Rationales - Kalai, Gil; Rubinstein, Ariel; Spiegler, Ran (Econometrica, 2002)
The paper presents a notion of rationalizing choice functions that violate the “Independence of Irrelevant Alternatives” axiom. A collection of linear orderings is said to provide a rationalization by multiple rationales for a choice function if the choice from any choice set can be rationalized by one of the orderings. We characterize a tight upper bound on the minimal number of orderings that is required to rationalize arbitrary choice functions, and calculate the minimal number for several specific choice procedures.